Calorie Restriction in Rodents: Caveats to Consider - Ingram, Donald K. (Ageing Res Rev, 2017)
The calorie restriction paradigm has provided one of the most widely used and most useful tools for investigating mechanisms of aging and longevity. By far, rodent models have been employed most often in these endeavors. Over decades of investigation, claims have been made that the paradigm produces the most robust demonstration that aging is malleable. In the current review of the rodent literature, we present arguments that question the robustness of the paradigm to increase lifespan and healthspan. Specifically, there are several questions to consider as follows: (1) At what age does CR no longer produce benefits? (2) Does CR attenuate cognitive decline? (3) Are there negative effects of CR, including effects on bone health, wound healing, and response to infection? (4) How important is schedule of feeding? (5) How long does CR need to be imposed to be effective? (6) How do genotype and gender influence CR? (7) What role does dietary composition play? Consideration of these questions produce many caveats that should guide future investigations to move the field forward.